Strengthening Students’ Moral Intelligence in the Digital Era: The Effects of Value Education and Religious Habituation in Islamic Elementary Schools - Nurjaman, Fauzi; Himmawan, Fajaruddin; Al Ishaq, Imam Abdimullah; Rasyid, Muhammad Azhari; Syahrin, Muhammad Alfi (Educational Research Center, 2026)
Moral challenges among school-age children have intensified in the digital era, making moral intelligence a crucial educational outcome. This study investigates the effects of values education and religious habituation on students’ moral intelligence at MI Al Qur’anul Hakim, Probolinggo, Indonesia. A quantitative approach with a causal explanatory survey design was employed. Data were collected from 70 students selected through purposive sampling from a population of 286. The instruments were closed-ended Likert-scale questionnaires measuring values education, religious habituation, and moral intelligence. Item validity was examined using item–total correlation, while internal consistency was assessed using Cronbach’s Alpha, showing strong reliability across all scales (α > 0.90). Data were analyzed using descriptive statistics and multiple linear regression with prerequisite tests. The findings reveal that values education has a positive and significant effect on students’ moral intelligence (β = 0.559, p < 0.001) and emerges as the strongest predictor. Religious habituation also contributes positively and significantly (β = 0.258, p = 0.043). Simultaneously, both predictors significantly influence moral intelligence (F = 52.0, p < 0.001), explaining 60.8% of the variance (R² = 0.608). These results highlight that strengthening students’ moral intelligence requires systematic integration of values education within classroom instruction and school culture, supported by meaningful religious habituation that emphasizes internalization rather than procedural routines. The study contributes empirical evidence to the growing literature on moral development in Islamic elementary education and offers practical implications for school-based character education strategies.